2021
DOI: 10.1155/2021/8880988
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Platelet Adhesion around Stent Struts in the Presence and Absence of Tissue Defects around Them

Abstract: Aim. To predict platelet accumulation around stent struts in the presence or absence of tissue defects around them. Methods. Computer simulations were performed using virtual platelets implementing the function of the three membrane proteins: glycoprotein (GP) Ibα, GPIIb/IIIa, and GPVI. These platelets were perfused around the stent struts implanted into the vessel wall in the presence or absence of tissue defects around them using within the simulation platform. The number of platelets that adhered around ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Studies have found that, as assessed by optical coherence tomography (OCT), stent malapposition (lack of contact between a stent strut and the intimal surface), neoatherosclerosis, uncovered struts and stent under-expansion were all higher in patients with LST and VLST [137]. Commonly, the underlying cause of LST and VLST was found to be due to multiple factors, with malapposition alongside uncovered struts being the most common, the precise mechanisms of which are not yet well understood but may be due to the tissue defect surrounding the uncovered struts [138]. However, plaque rupture and occlusive restenosis have been found to contribute [137,139].…”
Section: Thrombosismentioning
confidence: 98%
“…Studies have found that, as assessed by optical coherence tomography (OCT), stent malapposition (lack of contact between a stent strut and the intimal surface), neoatherosclerosis, uncovered struts and stent under-expansion were all higher in patients with LST and VLST [137]. Commonly, the underlying cause of LST and VLST was found to be due to multiple factors, with malapposition alongside uncovered struts being the most common, the precise mechanisms of which are not yet well understood but may be due to the tissue defect surrounding the uncovered struts [138]. However, plaque rupture and occlusive restenosis have been found to contribute [137,139].…”
Section: Thrombosismentioning
confidence: 98%
“…In addition, the effect of surface roughness on the initial adhesion of S690 low-alloy steel and epoxy-amine adhesive was studied by Van et al [16], the test results showed that the improved adhesion is mainly attributed to the increased surface area at higher surface roughness. Kawamura et al [17] investigated a higher rate of platelet adhesion in the presence of tissue defects around stent struts by computer simulation. Thus, the effect of defects on adhesion properties can't be ignored.…”
Section: Introductionmentioning
confidence: 99%